Pemberdayaan Masyarakat Kampung Warbor Distrik Supiori Utara Melalui Kegiatan KKL Mahasiswa FISIP UNCEN - Latif Karim; Rahmat Nurjaman; Alienra Davry Nanda Kadun MT (Lembaga Pengembangan Kinerja Dosen, 2025)
One of the community service activities that can be implemented by universities is the Field Work Lecture (KKL) program. The KKL program offers many positive benefits, including the opportunity to gain direct experience related to real-world work practices. We, along with fellow Office Administration Management students, were given the opportunity to carry out the KKL in Supiori Regency, specifically in North Supiori District, Warbor Village. The selection of Warbor Village as the KKL location was based on the desire to gain practical knowledge directly about administrative activities, as well as to be able to make a real contribution to the local community. In addition, this program also aims to strengthen good relations between students and the Warbor Village community. Through this KKL, students can better understand the application of theories learned in college in the context of the real world of work, and play an active role in helping solve problems in the community, especially in the field of administration. This activity is also expected to have a positive impact on the surrounding community and increase students' understanding of the important role of administration in everyday life.